Cultural Influences Of Baba-Nyonya On Eclectic Style Shophouse, George Town, Penang Case Study: Sun Yat Sen Museum - Zwain, Akram M.Ali Mahdi (2017)
China Peranakan or the Straits Chinese, is more well known as the Baba-Nyonya. They mainly revolve around Chinese and Malay cultures. However, the Baba-Nyonya culture features a hint of the people’s cultures of the Malay (Javanese, Batak), Thai and European (British and Dutch, Portuguese) cultures. Nevertheless, the supreme architectural achievement of this minority group i.e their eclectic shophouses is now facing a crisis which may determine its survival. The problem is critical for there is an inconsistently lack of sound knowledge in conservation of their shophouses.